Pedophilia Dalam Komik Toriko Aigan Shoujo Karya Mashin Osakabe - Ella Kumala Sari, Putu; Anita Dewi, Ni Made Andry; Damayanti, Silvia (Humanis; Vol 23 No 4 (2019)DO - 10.24843/JH.2019.v23.i04.p10, 2019)
The title of this research is “Pedophilia in Comic Toriko Aigan Shoujo by Mashin Osakabe”. The aims of this research are to describe the characteristic of pedophilia sexual disorders suffered by Shiren, as well as the impact that occurred on Shinju as a victim of pedophilia in Mashin Osakabe’s Toriko Aigan Shoujo comic. The theories that have been used are Endaswara’s Psychological Psychology (2010), Schmidth’s Pedophilia theory (2014) and Danesi’s Semiotic theory (2011). Based on the results, Takamagahara Shiren is an adult male who experiences one type of sexual disorder, namely pedophilia. Characteristics of pedophile sexual disorders in Shiren's character based on three dimensions, namely 1). Physiological dimensions are: heterosexual pedophiles and adult men who like a little girl; 2). The psychological dimension is: having a cruel and stubborn character, which can be seen from his behavior, uses various ways to be able to have sex with Shinju. In addition, Shiren's character is also ambitious take revenge on his mother by hurting Shinju; 3). The dimensions of sociology is: Shiren who closes himself to sociaty and dislikes social interaction. The impact experienced by Shinju as a pedophile victims occurred in the physical and psychological. The impact on the physical character of Shinju is the presence of injuries to the body. The impact of pedophilia on the psychology of Shinju are sexual addiction or hypersex, feeling self worthless, feeling ashamed and guilty that she often tries to commit suicide.